A Review of Tourists’ Dynamic Risk Perception Recognition: A Case Study of Eco-Environmental Health Factors - Peng, Yuting; Cao, Xinyu (International Journal of Natural Resources and Environmental Studies, 2025)
Background: This paper proposes a dynamic risk perception identification framework for tourists, focusing on dynamic research on risk perception related to environmental health factors, which overcomes the shortcomings of traditional data collection methods such as questionnaires and interviews, such as high cost, small sample size and large sample deviation. In this review, we aim to :(1) identify studies on dynamic risk perception of tourists using environmental health factors as examples; (2) Identify potential threats to the validity of the survey results; (3) Make suggestions for future planning, design and implementation. Methods: A range of censorship was conducted by searching CNKI and Web of Science with the keyword "tourist risk" to find tourist risk studies published before December 31, 2022. Potential research content is updated through January 2023 through other sources. A narrative statement of the results is combined with a descriptive summary of the characteristics of the study. Results: On China National Knowledge Network. We found 128 visitor risk studies, and on the Web of Science, there were 4,426 articles, 4,554 in total. The scope of the study is very wide and complex. Conclusions: We found that the research direction of tourists’ risk perception pays more attention to environmental health factors, but at the same time, the related research results of tourism risk are mainly concentrated in five aspects: tourism risk connotation, tourist risk, destination risk, stakeholder risk and tourism risk under the macro background. Tourists pay more attention to environmental problems and their impacts when choosing destinations. In recent years, tourists have paid more attention to environmental health factors, and it is necessary to better plan, implement and report mediation analysis.